2020
DOI: 10.3390/nu12092768
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mg2+ Extrusion Attenuates Glutamate Excitotoxicity in Cultured Rat Hippocampal Neurons

Abstract: Magnesium plays important roles in the nervous system. An increase in the Mg2+ concentration in cerebrospinal fluid enhances neural functions, while Mg2+ deficiency is implicated in neuronal diseases in the central nervous system. We have previously demonstrated that high concentrations of glutamate induce excitotoxicity and elicit a transient increase in the intracellular concentration of Mg2+ due to the release of Mg2+ from mitochondria, followed by a decrease to below steady-state levels. Since Mg2+ deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Intriguingly, it has been proposed that Mg 2+ is a major regulator of mTOR activity (De Baaij et al, 2015; Rubin, 2005), and evidence for this hypothesis is accumulating (Feeney et al, 2016; Funato et al, 2014; Hardy et al, 2019; Liu et al, 2021; Shindo et al, 2020; Sponder et al, 2018; Yamanaka et al, 2018). Perhaps the regulation of Mg 2+ and/or Mn 2+ levels provide a simple mechanism by which major cellular functions related to cell growth and replication can be controlled (Rubin, 2005).…”
Section: The Known Protein Partners Of Ole Rna Strengthen Links To Di...mentioning
confidence: 99%
“…Intriguingly, it has been proposed that Mg 2+ is a major regulator of mTOR activity (De Baaij et al, 2015; Rubin, 2005), and evidence for this hypothesis is accumulating (Feeney et al, 2016; Funato et al, 2014; Hardy et al, 2019; Liu et al, 2021; Shindo et al, 2020; Sponder et al, 2018; Yamanaka et al, 2018). Perhaps the regulation of Mg 2+ and/or Mn 2+ levels provide a simple mechanism by which major cellular functions related to cell growth and replication can be controlled (Rubin, 2005).…”
Section: The Known Protein Partners Of Ole Rna Strengthen Links To Di...mentioning
confidence: 99%
“…In previous studies, it has been demonstrated that glutamate-induced Ca 2+ response leads to depolarization of mitochondrial membrane potential and a decrease in the cellular ATP level. 52 However, the relationship between Ca 2+ levels, mitochondrial membrane potential, and ATP in each neuron has not been well discussed, because simultaneous imaging of those three signals had been difficult. Here, it was achieved by the combined use of KLCA-501 with between CFP and YFP, 32 and TMRE is a mitochondrial membrane potential probe with an orange fluorophore.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…However, due to the shallow concentration gradient of Mg 2+ across the membrane and the continuous exchange between their bound and the free form in the cytosol, changes in extracellular Mg 2+ availability can severely impact the intracellular Mg 2+ concentration and ribosomal functions. Also, the Mg 2+ deficiency within neurons can be sensed by mTOR signaling that can alter translation in several ways ( Shindo et al, 2020 ).…”
Section: Local Factors That Affect Translation Kineticsmentioning
confidence: 99%